Diasporic Female Bonding in Chitra Banerjee Divakarunis Sister Of My Heart - Irma Putri Aprilia (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Abstract This study analyzes the relationship between female characters, Anju and Sudha, in the Sister of My Heart novel by Chitra Banerjee Divakaruni. The female bonding displayed by Anju and Sudha are strong aspects that plot the story in the novel. This research analyzes how female bonding is portrayed in the novel and also how it affects Anju’s diasporic life and Sudha’s domestic life. To accommodate it, this research using one of the feminist survival strategy, female bonding, and also a branch of the Diaspora theory, the Diaspora consciousness. This study uses critical interpretation as data analysis. This analysis shows two conclusions, first, female bonding between Anju and Sudha is described from infancy, adolescence and until they become wives and mothers. Second, the influence of female bonding on Anju’s diasporic life and Sudhas domestic life remain strongly even though they live apart by American and Indian distances. Keywords: female bonding, feminist strategy, diaspora, diasporic consiousness Abstrak Studi ini menganalisa hubungan antar karakter wanita, Anju dan Sudha, dalam novel Sister of My Heart karya Chitra Banerjee Divakaruni. Ikatan perempuan yang ditampilkan oleh Anju dan Sudha merupakan aspek kuat yang menjadi plot cerita dalam novel. Penilitian ini menganalisa bagaimana ikatan perempuan digambarkan pada novel dan juga bagaimana ikatan perempuan mereka memengaruhi kehidupan diaspora Anju dan kehidupan rumah tangga Sudha. Untuk mengakomodisikannya, penelitian ini menggunakan salah satu strategi perempuan untuk bertahan hidup, yaitu ikatan perempuan, dan juga cabang dari teori Diaspora, yaitu kesadaran diaspora. Kajian ini menggunakan interpretasi kritis sebagai analisis data. Analisis ini menghasilkan dua kesimpulan, pertama, ikatan perempuan antara Anju dan Sudha digambarkan dari sejak bayi, remaja dan sampai saat mereka menjadi istri dan ibu. Kedua, pengaruh ikatan perempuan pada kehidupan diaspora Anju dan kehidupan rumah tangga Sudha tetap terjalin kuat walaupun mereka hidup terpisah oleh jarak Amerika dan India. Kata kunci: ikatan perempuan, strategi feminis, diaspora, kesadaran diaspora